Analysis of determinants of adherence to anti-tuberculosis drugs in tb patients during covid-19 at the public health center of Aceh Besar Regency - Amiruddin, Amiruddin; Ichwansyah, Fahmi; Hermansyah, Hermansyah; Maidar, Maidar; Abdullah, Asnawi (Science Midwifery, 2024)
The Covid-19 pandemic has had a significant impact on TB patients, particularly in terms of treatment and drug monitoring. During the pandemic in 2020, there were 350 cases of TB in Aceh Besar District. This study aimed to assess the compliance of TB patients during the Covid-19 period at the Aceh Besar District Health Center. A cross-sectional study design was employed, and data were collected from 118 TB patients from April to October 2020. The research was conducted in April 2022. Questionnaires were used for data collection, and bivariate and multivariate analyses were performed using the STATA 12 application program. The results of the multivariate analysis revealed that several risk factors, including Covid-19, history of illness, sources of information, age, knowledge, and trips to the health center, were associated with non-compliance in taking OAT medications. Efforts to increase awareness and educate the public about the risk factors of TB should continue, even during the Covid-19 pandemic. Building partnerships with former TB patients who have completed treatment and recovered can also help in promoting adherence to OAT medications among current TB patients.